Relationship Among Individual Characteristics, Access and Perception of Health Services for Selection of BPJS Referral Hospital with Hemodialysis Patients in Medan City - Siagian, Firsty Nanquita; Nasution, Siti Khadijah; Juanita, Juanita (RIRAI Publisher, 2025)
Choosing a BPJS referral hospital is an important decision for an individual who is sick and needs a more specific medical service for their illness. Hemodialysis is a replacement therapy for damaged kidney function that requires repeated actions. This study aims to determine how the influence of individual characteristics, access and perceptions of health services on the selection of BPJS referral hospitals for hemodialysis in Medan City. The type of research used in this study was an analytic survey with a cross-sectional study design, which was conducted on hemodialysis patients who underwent hemodialysis therapy at Malahayati Islamic Hospital, USU Hospital and Rasyida Kidney Specialty Hospital October 2024 with a sample of 100 people taken with accidental sampling technique. The results showed that education, income, hospital image, health worker services, patient safety, travel distance and hospital cleanliness/comfort had an influence on the selection of BPJS referral hospitals for hemodialysis in Medan City. Conduct information campaigns through social media, radio and print media to reach the wider community. The information delivered should be easy to understand and relevant to the needs of patients with renal failure and ensure that hemodialysis services are easily accessible to patients newly diagnosed with renal failure.